New Sharp Bounds for the Bernoulli Numbers and Refinement of Becker-Stark Inequalities - Hua-feng Ge (Journal of Applied Mathematics)
We obtain new sharp bounds for the Bernoulli numbers: 2(2n)!/(π2n(22n−1))<|B2n|≤(2(22k−1)/22k)ζ(2k)(2n)!/(π2n(22n−1)), n=k,k+1,…, k∈N+, and establish sharpening of Papenfuss's inequalities, the refinements of Becker-Stark, and Steckin's inequalities. Finally, we show a new simple proof of Ruehr-Shafer inequality.